Comparing Perceived Sleep Quality, Practices, and Behaviors of Male and Female Elite Rugby Union Athletes with the Use of Sleep Questionnaires - Teece, Angus R.; Beaven, Martyn; Argus, Christos K.; Gill, Nicholas; Driller, Matthew W. (Sleep Science, 2023)
Objective To evaluate the differences in subjective sleep quality, quantity, and behaviors among male and female elite rugby union athletes through two common sleep questionnaires.Materials and Methods A sample of 38 male and 27 female elite rugby union athletes filled out the Athlete Sleep Behavior Questionnaire (ASBQ) and the Pittsburgh Sleep Quality Index (PSQI). Global scores and individual items for each questionnaire were compared to assess differences between sexes.Results Male athletes reported significantly longer sleep duration (7 h 50 m ± 50 m versus 7h 12 m ± 58 m respectively; p ≤ 0.01; d = 0.70) and higher habitual sleep efficiency (88% versus 83% respectively; p < 0.05; d = 0.54) when compared with female athletes. Individual items of the ASBQ revealed significant differences between male and female athletes for five questions. Male athletes displayed higher instances of taking stimulants before training or competition and consuming alcohol within 4 hours of going to bed. Conversely, female athletes expressed greater thought or worry while in bed and a higher instance of training late at night.Discussion Male athletes displayed better self-reported sleep quality and quantity than female athletes; however, the present study highlighted that male and female elite rugby union athletes face specific challenges that differ. It appears that the differences observed between male and female elite rugby union athletes may be due to differing levels of professionalism or differences in training or competition schedules.
Keywords: team sports; sleep hygiene; sleep health; sleep education; athlete sleep behavior questionnaire; Pittsburgh sleep quality index